Update for the General Physician in the treatment of the HIV - Castro Danós, José (2024)
After two decades of availability of antiretroviral therapy, the prognosis of HIV-infected patients has changed dramatically. The curse of this infection has changed from a rapidly fatal infection to a more manageable, chronic infection with an almost normal life span. This has led to a dramatic reduction in the mortality rate related to HIV in countries where antiretroviral therapy is widely available. With incidence rates stable or increasing and lower mortality, the prevalence of this infection is increasing. This fact increases the chances of non-specialist physicians to encounter HIV infected patients in their practice. That is why this revision is directed to the non-specialist physician and its objective is to update their knowledge in the complex area of the management of HIV therapy. This is a broad but superficial revision of the current status of the management of HIV infection therapy, and includes the use of first line and alternative options of therapy as well as the description of two newly approved classes of antiretrovirals.